Deteksi Perakaran Kelapa Sawit Pada Lubang Biopori Modifikasi Dengan Metode Geolistrik Resistivitas - Yudhi Ahmad Nazari; Fakhrurrazie Fakhrurrazie; Noor Aidawati; Gunawan Gunawan (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
Palm has a fibrous root system, consisting of a primary root, secondary, tertiary and quaternary. In general, palm root system is closer to ground level, however, in certain cases it may penetrate deeper. One of the root functions is to absorb water and nutrients from the soil. Palm roots dispersion can be determined by using the geoeletric resistivity method. Geoelectric resistivity data using Wenner configuration method is measured in three trajectory forming an equilateral triangle on palm plant row with a variation of 9 m (AB / 2) in accordance with palm plant spacing, with potential electrode spacing of 30 cm (MN / 2). Collection of geoelectric resistivity data is done by injecting electric current into the earth through two electrodes, the potential difference is then measured through two potential electrodes. Measurements were performed by varying the distance of the electrodes and potentials, gradually from the smallest distance to the largest. Measurement of palm root dispersion detection consists of 3 tracks (L1, L2, and L3). Measurements on June 24, 2014 carried out on track 1 (L1) between rows of palm plants, track 2 (L2) between the palm plant within the same row, and track 3 (L3) diagonally between the rows of plants (Figure 1). Measurement on July 8, 2014 were on track 1 (L1) is between rows of palm plants, track 2 (L2) and track 3 (L3) diagonally between the rows of plants.Geoelectric on diagonal trajectory where modified biopore infiltration pit is in place resulted in low resistivity values. This is related to soil water availability, where it affects the development of the root towards the biopore pits.